2010
DOI: 10.1177/0165025409348560
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimization trajectories and their association with children’s affect in late elementary school

Abstract: The current study examined peer victimization trajectories for 1528 children from third to fifth grade and the association of those trajectories to children’s positive and negative affect. On average, victimization was low to moderate and remained stable (self-report) or increased (peer-reports). In addition, five distinct trajectories were identified based on self-report: Low, Moderate, Increasing, Decreasing, and Chronic. Peer-reported victimization did not reveal distinct trajectories. Although the level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 48 publications
(74 reference statements)
11
59
1
Order By: Relevance
“…Trajectory analyses revealed persistent, decreasing, and noninvolved victimization pathways in the intervention sample, mirroring previous research on victimization development in which the three-group model represented the best-fitting solution, with a small group of persistent victims, a larger group of individuals who were less victimized over time, and a large group of non-involved children (Barker et al, 2008b;Biggs et al 2010;Boivin et al 2010). In our sample, the group of children on a decreasing victimization pathway (15.3%) seemed large compared with previous studies.…”
Section: Predicting Trajectories Of Victimizationsupporting
confidence: 77%
“…Trajectory analyses revealed persistent, decreasing, and noninvolved victimization pathways in the intervention sample, mirroring previous research on victimization development in which the three-group model represented the best-fitting solution, with a small group of persistent victims, a larger group of individuals who were less victimized over time, and a large group of non-involved children (Barker et al, 2008b;Biggs et al 2010;Boivin et al 2010). In our sample, the group of children on a decreasing victimization pathway (15.3%) seemed large compared with previous studies.…”
Section: Predicting Trajectories Of Victimizationsupporting
confidence: 77%
“…Giesbrecht et al () found that social victimization may decline from first through third grade. In contrast, the findings of Biggs et al () suggest that this form of victimization may slightly increase from third through fifth grade. Additional research is needed to examine the development of social victimization across the transition to adolescence.…”
Section: Longitudinal Examinations Of Victimizationmentioning
confidence: 84%
“…We expected social victimization trajectories to be similar to those found in earlier work on general victimization. Based on past research we expected to find a low, increasing, and decreasing trajectory (Barker, Arsenault et al, ; Biggs et al, ; Boivin et al, ). Further, we hypothesized that we might find an elevated group (Biggs et al, ).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Three to five different trajectories have been uncovered through the small but growing body of research in this area. Prior work, though providing insights into developmental models of victimization, has been limited to specific periods in the life course including childhood (Biggs et al, 2010;Boivin et al, 2010;Leadbeater and Hoglund, 2009), adolescence (Brooks-Russell et al, 2013;Higgins et al, 2009;Jennings et al, 2010;Smith and Ecob, 2007;Sullivan et al, 2011), and college years (Swartout et al, 2012). Further inquiry is therefore needed to expand the time frame in which victimization is examined.…”
Section: Introductionmentioning
confidence: 99%